2021
DOI: 10.4236/jcdsa.2021.112011
|View full text |Cite
|
Sign up to set email alerts
|

Porcine Placenta Extract Reduced Wrinkle Formation by Potentiating Epidermal Hydration

Abstract: Background: Placenta extract is used as an alternative medicine especially in Asian countries as it is a rich reservoir of diverse bioactive molecules. The effects of placenta extract on skin conditions have been previously reported, however, the mechanism underlying for reduced wrinkle formation remains unclear. Objective: The primary objective of this study was to determine whether the continuous application of porcine placenta extract (PPE) alleviates wrinkle formation in humans and explore the underlying m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 15 publications
1
7
0
Order By: Relevance
“…In this study, we demonstrated, for the first time, the underlying mechanism of PPE function and provided scientific evidence for the application of PPE in alternative medicine. Combined with our previous study showing that applying a gel containing placental extract to humans increases the water content in the stratum corneum [13], this study suggests that placental extract improves skin barrier function by increasing ceramide contents via the upregulation of CerS3 expression level. However, further research to show that placental extract increases ceramide in human skin in vivo is required.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…In this study, we demonstrated, for the first time, the underlying mechanism of PPE function and provided scientific evidence for the application of PPE in alternative medicine. Combined with our previous study showing that applying a gel containing placental extract to humans increases the water content in the stratum corneum [13], this study suggests that placental extract improves skin barrier function by increasing ceramide contents via the upregulation of CerS3 expression level. However, further research to show that placental extract increases ceramide in human skin in vivo is required.…”
Section: Discussionsupporting
confidence: 79%
“…CerS3, which is one of the six distinct isoforms of CerSs, is highly expressed in keratinocytes, synthesizes ceramides containing α-hydroxy fatty acids, and is involved in maintaining skin bar-rier function [14] [15] [16]. We have recently reported that PPE, which is widely used in alternative and traditional medicine, enhances CerS3 expression [13].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CerS3 expression [13]. However, because the regulation of CerS3 expression is largely uncharacterized, we explored the underlying mechanism of the PPE-induced upregulation of CerS3 in this study.…”
Section: Discussionmentioning
confidence: 99%
“…CerS3, which is one of the six distinct isoforms of CerSs, is highly expressed in keratinocytes, synthesizes ceramides containing α-hydroxy fatty acids, and is involved in maintaining skin barrier function [14-16]. We have recently reported that PPE, which is widely used in alternative and traditional medicine, enhances CerS3 expression [13]. However, because the regulation of CerS3 expression is largely uncharacterized, we explored the underlying mechanism of the PPE-induced upregulation of CerS3 in this study.…”
Section: Discussionmentioning
confidence: 99%